2009
DOI: 10.1167/iovs.08-3294
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Severity of Distance and Near-Vision Impairment on Depression and Vision-Specific Quality of Life in Older People Living in Residential Care

Abstract: VI remains a major form of disability in individuals living in residential care facilities and affects vision-specific functioning and socioemotional aspects of daily living. A larger study is needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 39 publications
(46 reference statements)
3
67
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12] Major causes of irreversible blindness such as retinal diseases, glaucoma, age-related macular degeneration (ARMD) as well as reversible causes like cataract are common in nursing homes. It is vital that vision care not be ignored in this population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12] Major causes of irreversible blindness such as retinal diseases, glaucoma, age-related macular degeneration (ARMD) as well as reversible causes like cataract are common in nursing homes. It is vital that vision care not be ignored in this population.…”
Section: Introductionmentioning
confidence: 99%
“…1,12,13 VI has significant and deleterious impact on quality of life (QoL) and reduces vision-related QoL. 2,3,5,6,14 Vision-related QoL is the present visual status and the limitations in daily living activities like personal hygiene, communication, self-care, social skills, mobility, safety etc. as perceived by the subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the effect of aging, vision loss may not only lead to difficulties in performing activities [11][12][13][14][15][16][17] but also to loss of activities [18,19], dependency [20][21][22] and social isolation [23]. Vision loss is related to depression [24][25][26][27] and emotional distress [28] and has a negative impact on health-related quality of life [15,[28][29][30][31][32][33]. Besides, it is regarded an important factor of disability [23].…”
Section: Introductionmentioning
confidence: 99%
“…As in these studies, those who had difficulty with seeing were found to be older (Horowitz et al, 2005;Jin & Wong, 2008), disproportionately female (Evans et al, 2002;Horowitz et al, 2005;Michon et al, 2002;Nirmalan et al, 2002;Oye & Kuper, 2007;Song et al, 2010;Wong et al, 2008), and to have a poorer perception of health (Chia et al, 2004;LaGrow et al, 2009;J. J. Wang et al, 2000) and lower rating of QOL (Bekibele & Gureje, 2008a;LaGrow, Alpass, Stephens, & Towers, 2011a;LaGrow et al, 2011b;Lamoureux, Fenwick, Moore, Klaic, Borschmann, & Hill, 2009;Nutheti, Shamanna, Nirmalan, Keeffe, Krishnaiah, Rao, & Thomas, 2006;Tran, Mahdi, Sivasubramaniam, Gudlavalleti, Gilbert, Shah, Ezelum, Abubakar, & Bankole, 2011;C. W. Wang, Chan, Ho, & Xiong, 2008) than those who were not.…”
Section: Discussionmentioning
confidence: 90%